Prevalensi Kekurangan Energi Kronis pada Ibu Hamil di Kota Salatiga Tahun 2020 - Renyoet, Brigitte Sarah; Tampubolon, Rifatolistia; Sijabat, Yulinda Dwi Lestari (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: Chronic Energy Deficiency (CED) is a condition in which the mother experiences a prolonged/chronic lack of food, which can lead to CED in pregnant women. Pregnant women with CED will be at risk of experiencing health problems for the mother and fetus, and even death. The aim of the study was to determine the prevalence of CED pregnant women in Salatiga City in 2020.Methods: The research used is descriptive quantitative research with a cross sectional research approach which was conducted in Salatiga City. The data were obtained through secondary data in 2020 from the Salatiga City Health Center in February 2021 and July 2021. Respondents in the study were pregnant women who experienced CED in Salatiga city with LILA conditions <23.5 cm, the data obtained were calculated according to the formulaResult: The percentage of pregnant women with CED in the City of Salatiga in 2020 as much as 9.1% where these results when compared to WHO achievements are included in the mild category of health problems (<10%).Conclusion : There is an increase in the prevalence of CED in pregnant women in Salatiga City between 2018 and 2020 as much as 2.66%. The incidence of CED in pregnant women mostly occurs at the best age for pregnancy, namely the age of 20-35 years in the first trimester, it is necessary to pay attention through Puskesmas programs related to pregnancy nutrition education so that it is hoped that the incidence of CED in Salatiga City can decrease.